Earnings quality determinants in the Jordanian service sector (The financial crisis during Corona crisis) - Mohammad Ahmad Alqam; Walid Omar Owais; Haitham Yousef Ali; Yaser Mohd Hamshari (Cogent Business & Management, 2022)
This study examined the impact of financial ratios, represented by liquidity, retained earnings ratio, profitability ratio, debt ratio, and total assets turnover, on earnin gs quality. This study involved 45 service companies registered between 2014 and 2020. Purposive sampling was used for 41 firms and 287 analytical units. Descriptive statistics and moderated regression were used. The findings showed that financial ratios affect the quality of earnings. Governance strategies can affect earnings quality along with financial ratios. The result of this study recommended that future researchers use a combination of methods to check the financial statement data. In addition, this study suggested that to get managers to smooth out their earnings; managers should have more control over financial ratios.
Keywords: 650; earning quality; financial ratio; governance mechanism; moderated regression analysis